Can ultralight dark matter explain the age–velocity dispersion relation of the Milky Way disc: A revised and improved treatment. Issue 3 (21st November 2022) - Chiang, Barry T; Ostriker, Jeremiah P; Schive, Hsi-Yu
ABSTRACT: Ultralight axion-like particles ma ∼ 10 −22 eV, or Fuzzy Dark Matter (FDM), behave comparably to cold dark matter (CDM) on cosmological scales and exhibit a kpc-size de Broglie wavelength capable of alleviating established (sub-)galactic-scale problems of CDM. Substructures inside an FDM halo incur gravitational potential perturbations, resulting in stellar heating sufficient to account for the Galactic disc thickening over a Hubble time, as first demonstrated by Church et al. We present a more sophisticated treatment that incorporates the full baryon and dark matter distributions of the Milky Way and adopts stellar disc kinematics inferred from recent Gaia, APOGEE, and LAMOST surveys. Ubiquitous density granulation and subhalo passages, respectively, drive inner disc thickening and flaring of the outer disc, resulting in an observationally consistent 'U-shaped' disc vertical velocity dispersion profile with the global minimum located near the solar radius. The observed age–velocity dispersion relation in the solar vicinity can be explained by the FDM-substructure-induced heating and places an exclusion bound ma ≳ 0.4 × 10 −22 eV. We assess non-trivial uncertainties in the empirical core–halo relation, FDM subhalo mass function and tidal stripping, and stellar heating estimate. The mass range ma ≃ 0.5–0.7 × 10 −22 eV favoured by the observed thick disc kinematics is in tension with several exclusion bounds inferred from dwarf density profiles, stellar streams, and Milky Way satellite populations, which could be significantly relaxed due to the aforesaid uncertainties. Additionally, strongly anisotropic heating could help explain the formation of ultra-thin disc galaxies.